Lean thinking applied to a high-mix low-volume environment: CR technology System case study - Riccardi, Giulia (2023)
This thesis was written during an internship at CR Technology system, at the headquarters in Bergamo, Italy. CR Technology System is a company that has been operating in the energy generation, provision and distribution sector since 1985 and developed strong skills that are recognized and appreciated worldwide. It is a company that invests heavily in research and development and therefore offers customers turn-key and tailor-made products and solutions, for the production, transformation, and distribution of energy. Today it is going through a transition phase by focusing its business more and more on the renewable energy sector that represents great growth potential for the company in terms of orders and turnover, but it is causing difficulties in planning and control of orders and departments. For this reason, the management team has decided to try adopting some of the techniques of Lean Thinking, adapting them to the High-mix low-volume context to which CRTs belong to. It is well known that it is difficult to apply these methods to companies that work on orders nevertheless, the proposed approach involving the use of Setsuban Kanri, planning and control system that makes use of Visual Management, was considered interesting. The latter facilitates the circulation of information, the understanding of priorities, work progresses, and also spreads a climate of cooperation among the managers using it.. This thesis served to uproot traditional approaches, bring problems to the surface from below and give an impetus to innovation from the point of view of structure and corporate planning.